Codevelopment of a complex intervention to reduce inequalities in paediatric diabetes secondary care outcomes for children with type 1 diabetes from underserved groups - Ian Litchfield; Timothy Barrett; Sheila Greenfield; Sabi Redwood; S Uday; T Barrett; Aidan Searle; J Wheeler; Julian P H Shield; T Moore; P Sundaram; F Campbell; et al. (BMJ Open)
Objectives To codevelop (with children and young people with diabetes (CYPD)) an intervention to improve diabetes control and future health outcomes of CYPD from ‘underserved’ groups, to reduce treatment outcome inequalities between different socioeconomic and ethnic groups. To follow Medical Research Council guidance for complex interventions and the COM-B (Capability, Opportunity, Motivation, Behaviour) model for behaviour change intervention development.Design In phase 1 (previously reported), we established the evidence base, conducted literature reviews and analysed data from semistructured interviews with CYPD and their carers. In phase 2 (this report), we applied the COM-B framework to identify intervention components; in phase 3 (this report), we evaluated these components, including focus groups with CYPD, their carers’ and healthcare practitioner (HCP) surveys, using the Acceptability, Practicability, Effectiveness, Affordability, Spill-Over Effects, Equity criteria.Setting Secondary care; children, young people and their carers’ were approached from two large paediatric diabetes services in England, both with socioeconomically and ethnically diverse underserved populations; paediatric diabetes HCPs were surveyed across four English regions.Participants N=69 underserved CYPD (aged 5–19 years) and/or family members took part in interviews; N=48 paediatric diabetes HCP survey respondents (survey 1); N=34 paediatric diabetes HCP survey respondents (survey 2); N=3 young people’s advisory group participants; N=17 underserved CYPD/carers focus group participants; N=9 wider stakeholder participants.Results The codevelopment process and integration of COM-B established four elements for an intervention package: (1) an enhanced peer support/mentoring programme; (2) provision of a health and well-being coach to CYPD/families; (3) family/community support to address social and community issues and (4) training for HCPs, including cultural competence, poverty proofing and to emphasise the need for increased sensitivity and better supported communication in work with CYPD from underserved groups.Conclusions The Diversity in Diabetes codevelopment work informed an intervention to improve diabetes care in underserved groups, reflecting sociocultural contexts and plausible support options at the individual, community and clinical levels. The ‘Diversity in Diabetes’ programme will next test feasibility and further refine the intervention package in two more paediatric diabetes centres in England.